Features of the oral microbiome in Japanese elderly people with 20 or more teeth and a non-severe periodontal condition during periodontal maintenance treatment: A cross-sectional study - Toyama, Naoki; Ekuni, Daisuke; Yokoi, Aya; Fukuhara, Daiki; Islam, Md Monirul; Sawada, Nanami; Nakashima, Yukiho; Nakahara, Momoko; Sumita, Ichiro; Morita, Manabu (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction The aim of the present study was to characterize the profile and diversity of the oral microbiome of a periodontally non-severe group with ≥20 teeth in comparison with a severe periodontitis group of elderly Japanese people. Methods A total of 50 patients who had ≥20 teeth and aged ≥60 years were recruited, and 34 participants (13 non-severe participants) were analyzed. After oral rinse (saliva after rinsing) sample collection, the V3–V4 regions of the 16S rRNA gene were sequenced to investigate microbiome composition, alpha diversity (Shannon index, Simpson index, richness, and evenness), and beta diversity using principal coordinate analysis (PCoA) based on weighted and unweighted UniFrac distances. A linear discriminant analysis effect size was calculated to identify bacterial species in the periodontally non-severe group. Results The periodontally non-severe group showed lower alpha diversity than that of the severe periodontitis group (p <0.05); however, the beta diversities were not significantly different. A higher relative abundance of four bacterial species (Prevotella nanceiensis, Gemella sanguinis, Fusobacterium periodonticum, and Haemophilus parainfluenzae) was observed in the non-severe group than that in the severe periodontitis group. Conclusion The oral microbiome in elderly Japanese people with ≥20 teeth and a non-severe periodontal condition was characterized by low alpha diversity and the presence of four bacterial species.